Green HRM, psychological green climate and pro-environmental behaviors: An efficacious drive towards environmental performance in China - Naz, Shumaila; Jamshed, Samia; Nisar, Qasim Ali; Nasir, Nadia (Current psychology (New Brunswick, N.J.), 2023)
This study is undertaken to examine that how Green human resource management practices heightens environmental performance via employees’ psychological green climate and pro-environmental behaviors. It also assesses the moderating role of environmental knowledge between pro-environmental behaviors and organizational environmental performance that was almost unnoticed in the preceding studies. Data were collected from the employees who were directly engaged with the implementation of green practices in manufacturing firms located in Jiangsu, China. 450 employees completed the questionnaires and finally, 370 valid responses the green HRM practices were used for the PLS-SEM analysis. The analytical findings revealed that the green HRM practices and corporate environmental strategy are positively related to the psychological green climate that subsequently leads to generate pro-environmental behaviors in employees. Furthermore, the results shed light on the precise development of the corporate level environmental strategy to motivate employees for the creation of an eco-friendly workplace leading to optimizing environmental performance. Further, results postulate that environmental knowledge moderates between pro-environmental behaviors and environmental performance. This research is an extension of existing literature by adding the predictor of corporate environmental strategy as one of the significant antecedents of pro-environmental behaviors and environmental performance. Secondly, it contributes to the existing body of literature through the incorporation of environmental knowledge as a moderator between pro-environmental behaviors and environmental performance. This research study provides valuable practical implications to the top management, and policymakers for ensuring the commitment of employees towards implementation of Green human resource management practices and corporate environmental strategy to achieve environmental performance.